Toxicity after moderately hypofractionated versus conventionally fractionated prostate radiotherapy: A systematic review and meta-analysis of the current literature. (September 2021) - Francolini, G.; Detti, B.; Becherini, C.; Caini, S.; Ingrosso, G.; Di Cataldo, Vanessa; Stocchi, G.; Salvestrini, V.; Lancia, A.; Scartoni, D.; Giacomelli, I.; Sardaro, A.; et al.
Graphical abstract: Highlights: 13 studies comparing moderate hypofractionation and conventional fractionation prostate cancer patients were included. Pooled analysis about acute toxicity was performed. Narrative overview of late toxicity was reported. Majority of trials included in our meta-analysis suggested that moderately hypofractionated RT is equivalent, in terms of GI and GU adverse events, to conventional fractionation. Pooled analysis showed a 9.8 % and 1.5 % increase in acute GI and GU toxicity, respectively. Results may have been influenced by effect of to dose escalation rather than hypofractionation. Abstract: Background: Moderately hypofractionated radiotherapy (RT) currently represents the standard RT approach for all prostate cancer (PCa) risk categories. We performed a systematic review and meta-analysis of available literature, focusing on acute and late genitourinary (GU) and gastrointestinal (GI) adverse events (AEs) of moderate hypofractionation for localized PCa. Materials and methods: Literature search was performed and two independent reviewers selected the records according to the following Population (P) Intervention (I) Comparator (C) and Outcomes (O) (PICO) question: "In patients affected by localized PCa (P), moderately hypofractionated RT (defined as a treatment schedule providing a single dose per fraction of 3–4.5 Gy) (I) can be considered equivalent to conventionally fractionated RT (C) in terms of G > 2 GI and GU acute and late adverse events (O)?". Bias assessment was performed using Cochrane Cochrane Collaboration's Tool for Assessing Risk of Bias. Results: Thirteen records were identified and a meta-analysis was performed. Risk of acute GI and GU > 2 adverse events in the moderately hypofractionated arm was increased by 9.8 % (95 %CI 4.8 %–14.7 %; I 2 = 57 %) and 1.5 % (95 % CI -1.5 %-4.4 %; I 2 = 0%), respectively. Discussion: Overall, majority of trials included in our meta-analysis suggested that moderately hypofractionated RT is equivalent, in terms of GI and GU adverse events, to conventional fractionation. Pooled analysis showed a trend to increased GI toxicity after hypofractionated treatment, but this might be related to dose escalation rather than hypofractionation.